Optical triggered seizures using a caged 4-Aminopyridine - Zhao, Mingrui; McGarry, Laura M.; Ma, Hongtao; Harris, Samuel; Berwick, Jason; Yuste, Rafael; Schwartz, Theodore H. (Frontiers in Neuroscience, 2015)
Animal models of epilepsy are critical not only for understanding the fundamental mechanism of epilepsy but also for testing the efficacy of new antiepileptic drugs and novel therapeutic interventions. Photorelease of caged molecules is widely used in biological research to control pharmacologic events with high spatio-temporal resolution. We developed a technique for in vivo optical triggering of neocortical seizures using a novel caged compound based on ruthenium photochemistry (RuBi-4AP). Epileptiform events were induced with blue light illumination. Multi-electrode array recording and optical techniques were used to characterize the propagation of these epileptic events. Epileptiform events including interictal spikes, polyspikes, and ictal discharges were induced with blue light illumination. This model can be induced in vivo with both whole brain and focal illumination to provide high spatio-temporal control of the site of ictal onset. These results demonstrate a novel optically-triggered seizure model that may have widespread application in the investigation of ictal onset, propagation and in novel light-based therapeutic interventions.